2022
DOI: 10.20944/preprints202211.0519.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Using Machine Learning to Improve Performance of a Low-Cost Real-Time Stormwater Control Measure

Abstract: The alteration of natural land cover to impervious surfaces during development increases stormwater runoff. Stormwater Control Measures (SCMs) are used to manage water quantity and enhance water quality by restoring the hydrologic cycle altered by development. Often, SCMs have an outflow pipe to handle overflows or to manage the release of water detained when infiltration is not possible. Traditionally, these are static controls (e.g. a small orifice is used to restrict the volume of outflow), however, these s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…In this research, a neural network with one LSTM hidden unit accompanied by a dense layer connecting the LSTM target output at the last time-step (t-1) to a single output neuron with non-linear activation function. The LSTM model was trained using the deep learning library, Keras in Python, and the RMSE, and MAE [54][55][56][57][58]. To predict the discharge variable of a time-step in the future daily values of the variables at the previous time-steps are used.…”
Section: Long Short-term Memory (Lstm) Recurrent Neuralmentioning
confidence: 99%
“…In this research, a neural network with one LSTM hidden unit accompanied by a dense layer connecting the LSTM target output at the last time-step (t-1) to a single output neuron with non-linear activation function. The LSTM model was trained using the deep learning library, Keras in Python, and the RMSE, and MAE [54][55][56][57][58]. To predict the discharge variable of a time-step in the future daily values of the variables at the previous time-steps are used.…”
Section: Long Short-term Memory (Lstm) Recurrent Neuralmentioning
confidence: 99%
“…LSTM model have already been used as a very advanced model in the field of DL, e.g., speech recognition, natural language processing, automatic image captioning and machine translation [44,54,55]. However, only a few studies have applied Recurrent Neural Networks (RNNs) or LSTMs to forecast multivariate time series data in the field of water resource [56][57][58]. The objective of this research is to untangle the pattern of the temporal distribution and linkage among the aforementioned SW variables and perform predictive analysis on the using the previous observed data.…”
Section: Introductionmentioning
confidence: 99%
“…The LSTM model has been employed extensively in various fields of deep learning, such as speech recognition, natural language processing, automatic image captioning, and machine translation, showcasing its advanced capabilities [47,56,57]. In the realm of water resource forecasting, there have been limited instances where researchers have utilized Recurrent Neural Networks (RNNs) or LSTMs to predict multivariate time-series data [58][59][60]. The objective of this research is to untangle the pattern of the temporal distribution and the relation among the selected SW (surface water) variables for this study; as well as perform predictive analysis using observed data.…”
Section: Introductionmentioning
confidence: 99%